IMPLEMENTASI WEB-BASED TRANSPORTATION MANAGEMENT SYSTEM DI INDUSTRI TRANSPORTASI: SEBUAH TINJAUAN SISTEMATIS LITERATUR - jusnidar jusnidar; Riskayanti Riskayanti; Yudhika Setiawan; Kharismatul Khomsiah; Amsar Diath Yogmar; Dhimas Tribuana (Plexi Digital Indonesia, 2025)
This systematic literature review examines the implementation of Web-Based Transportation Management Systems (Web-TMS) to identify key technologies, methodologies, and factors influencing operational efficiency in modern transportation industries. The research method refers to the PRISMA 2020-2025 guidelines, including the stages of identification, screening, and thematic synthesis of 20 relevant scientific articles The reviewed literature highlights various modern approaches, including transportation network optimization (Bešinović, 2020), the application of artificial intelligence for mobility planning (Guevara & Cheein, 2020; Humayun et al., 2022), and the integration of big data and predictive models in traffic management systems (Wu et al., 2022; Yang et al., 2020). Several studies also emphasize the importance of real-time monitoring, fleet management, and operational automation to improve service reliability (Gohar & Nencioni, 2021; Skibniewski et al., 2014). Other references focus on sustainability and infrastructure resilience, including energy efficiency and advanced materials in modern transportation systems (Oladimeji et al., 2023; Rudskoy et al., 2021; Heinbach et al., 2022). Overall, this literature review indicates that the implementation of a web-based Transportation Management System is a strategic approach to addressing the increasing complexity of contemporary transportation, as it integrates route optimization, real-time tracking, data-driven analytics, and intelligent decision-making into a single platform. This integration not only enhances operational efficiency but also supports sustainability and digital transformation in the transportation sector.